Simultaneous design of parameters and controller of robotic manipulators: closed loop approach to practical implementation. (1st February 2018) - Moradi, M.; Naraghi, M.; Kamali E., A.
Abstract: In this paper, Simultaneous Design of Plant parameters and Controller (SDPC) of robotic manipulators is presented using the Closed Loop (CL) optimal control approach. Since a robot is inherently used to perform repetitive tasks, the SDPC problem for robotic manipulator systems is practically reformulated as the optimal balancing problem and a demonstration of practical implementation. The optimality conditions are derived using the CL-optimal control theory and then solved by the policy iteration method. The modified policy iteration is further used to design robot parameters. The results are compared with the Open Loop (OL) solution through the optimal and static balancing cases. As a final point, although OL is the exact solution, but it has higher control cost over the CL implementation (for the case implemented here the cost difference is 16.75%). Also CL-case has much shorter calculation time (51%) than that of the OL case. Abstract :